Community Development Guidelines with a Focus on Sustainable Tourism: A Case Study of the Hua Takae Old Market Community - Ubonsri, Benjawan; Daungthima, Wittaya (Journal of Architectural/Planning Research and Studies (JARS), 2023)
The main objective of this study is to analyze development potentials for the Hua Takae Market Community in order to develop guidelines for strong and self-reliant development. The development concept allowed local residents to participate in and be a part of the guideline development. Research methods included a study of the community’s existing physical, geographical social, and economic aspects, analysis, and setting up community goals and finally development of community tourism guidelines. The results indicate that there are two main development ideas, these being the community development concept and tourism guidelines. The community development concept covers suggestions for facility development that address the needs of both local residents and tourists. The tourism guidelines cover proposed tourist routes and a year-round activity schedule. The proposed method and development is expected to generate higher income for local residents, and give tourists the opportunity to visit and understand traditional lifestyle and culture.